Analisis Selling Skill terhadap Penjualan Produk Asuransi Bank BCA Trunojoyo Jember - Ardi Wiranata; Lingga Yuliana (Master Manajemen, 2025)
This study aims to analyze the selling skills of marketing officers in the process of selling insurance products at BCA Trunojoyo Branch. It is a qualitative descriptive study. The respondents are insurance marketing officers assigned to the BCA Trunojoyo branch in Jember. The data source used is primary data, which was obtained through interviews with the insurance marketing officers at the BCA Trunojoyo branch in Jember, conducted in April 2025. The results of the study indicate that the selling skills possessed by each individual selling skills have a crucial role in enhancing the success of insurance product sales. By implementing the development of good selling skills for marketing staff, it is hoped that Bank BCA Trunojoyo Jember can improve the quality of marketing staff periodically through training so that they can meet the company's goals and be able to maintain competitiveness in the banking sector, especially the sale of insurance products.